La fin du monde hippocratique? Contribution à la question de la concept de maladie entre la Renaissance et le 19e siècle (Theatrum historiae, 2013)
The study introduces the basic outline of conceptions and characteristics of historical approaches to origin of illness and contagion. Essential were primarily the decomposition of ancient Hippocratic-Galen paradigm and the birth of a new model of consideration and defining of illness in the period between the Renaissance and the mid-19th century. We focus on three issues: the question of the definition of illness; efforts to create “nosological” classification schemes; efforts to understand the disease contagion, and the transmission and spread of disease.